Comparative Analysis of Antioxidants in Moringa Leaves and Soursop Leaves - Kamaluddin, Irna Diyana Kartika; Ramadhani, Pratiwi Trisda; Bima, Irmayanti Haidir; Irwan, Andi Alamanda; Matoo, Rasfayanah F. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Antioxidants are chemical compounds that can donate one or more electrons to free radicals, so antioxidants function to neutralize free radicals. Antioxidants delay and inhibit cell damage through their properties that can neutralize free radicals. Several studies have reported that M.oleifera has antioxidant activity to various pharmacological effects such as anti-inflammatory and anti-cancer. Moringa oleifera or better known as Moringa is a plant that is widely used by the community to overcome various disease complaints. In addition to Moringa leaves, Soursop leaves (Annona muricata L) also have high antioxidant content in their leaves so that these plants can be divided into synthetic antioxidants and natural antioxidants. The use of synthetic antioxidants is currently decreasing due to consideration of the negative effects on health such as liver damage and can cause carcinogens so that their use is replaced by natural antioxidants. The natural antioxidants in question are compounds found in natural materials such as Moringa leaves and Soursop leaves. The type of research used in this study is experimental research by testing the comparison of antioxidant compound activity between Moringa leaves and Soursop leaves using the DPPH method. Moringa leaves had antioxidant activity of 141.34 ppm, while Soursop leaves had antioxidant activity of 82.39 ppm. There is no significant difference in antioxidant activity between Moringa leaves and Soursop leaves.